Odpowiedzi

Najlepsza Odpowiedź!
2010-01-13T17:58:33+01:00
(x+y=9
(X-Y=3

(x+y=9
(x=3+y

(3+y+y=9
(x=3+y

3+2y=9
x=3+y

2y=9-3
x=3+y

2y=6
x=3+y

y=3
x=3+3

y=3
x=6

spr. 6+3=9; 6-3=3

(x+4y=11
(2x+5y=10

x=11-4y
2x+5y=10

x=11-4y
2*(11-4y)+5y=10

x=11-4y
22-8y+5y=10

x=11-4y
22-3y=10

x=11-4y
-3y=-12

x=11-4y
y=4

x=11-4*4
y=4

x=11-16
y=4

x=-5
y=4

spr. -5=4*4=-5+16=11; 2*(-5)+5*4=-10+20=10

(3x+2y=2
(-3x+y=10

3x+2y=2
y=10+3y

3x+2*(10+3y)=2
y=10+3y

3x+20+6y=2
y=10+3y

9x=-18
y=10+3y

x=-2
y=10+3*(-2)

x=-2
y=10-6

x=-2
y=4

spr. 3*(-2)+2*4=-6+8=2; -3*(-2)+4=6+4=10